Combining 3D human in vitro methods for a 3Rs evaluation of novel titanium surfaces in orthopaedic applications. Issue 7 (21st January 2016) - Stevenson, G.; Rehman, S.; Draper, E.; Hernández‐Nava, E.; Hunt, J.; Haycock, J.W.
ABSTRACT: In this study, we report on a group of complementary human osteoblast in vitro test methods for the preclinical evaluation of 3D porous titanium surfaces. The surfaces were prepared by additive manufacturing (electron beam melting [EBM]) and plasma spraying, allowing the creation of complex lattice surface geometries. Physical properties of the surfaces were characterized by SEM and profilometry and 3D in vitro cell culture using human osteoblasts. Primary human osteoblast cells were found to elicit greater differences between titanium sample surfaces than an MG63 osteoblast‐like cell line, particularly in terms of cell survival. Surface morphology was associated with higher osteoblast metabolic activity and mineralization on rougher titanium plasma spray coated surfaces than smoother surfaces. Differences in osteoblast survival and metabolic activity on titanium lattice structures were also found, despite analogous surface morphology at the cellular level. 3D confocal microscopy identified osteoblast organization within complex titanium surface geometries, adhesion, spreading, and alignment to the biomaterial strut geometries. Mineralized nodule formation throughout the lattice structures was also observed, and indicative of early markers of bone in‐growth on such materials. Testing methods such as those presented are not traditionally considered by medical device manufacturers, but we suggest have value as an increasingly vital tool in efficiently translating pre‐clinical studies, especially in balance with current regulatory practice, commercial demands, the 3Rs, and the relative merits of in vitro and in vivo studies. Biotechnol. Bioeng. 2016;113: 1586–1599. © 2015 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc. Abstract : Stevenson and coworkers report on a combination of 3D in vitro methods for evaluation and assessment of novel orthopedic biomaterial implants made by additive manufacturing. The novelty of this approach uses normal human osteoblasts and 3D imaging of the biomaterial‐cell interface with measurement of osteoblast viability, metabolic activity, adhesion, cytoskeletal organization, and mineral formation. This approach increases the rapidity of biomaterials selection, and addresses the 3Rs, which allows more focused in vivo and pre‐clinical follow‐on studies to be conducted.